PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA WORDWALL UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS II UPT SD NEGERI TERGAMBANG - Nur Hidayah; Saeful Mizan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to improve the mathematics learning outcomes of second-grade students at UPT SD Negeri Tergambang through the implementation of a Problem-Based Learning model supported by Wordwall in the 2024/2025 academic year. This classroom action research was conducted in two cycles consisting of four stages: planning, implementation, observation, and reflection. The subjects of this study were second-grade students at UPT SD Negeri Tergambang. The data analyzed in this study included observation data on teacher activities, student activities, and learning outcomes. Descriptive, qualitative, and quantitative methods were used to analyze the data. The results showed that the students' learning outcomes in the pre-cycle phase were 42.86% of 14 students. In Cycle I, 64.28% of students achieved learning outcomes, indicating an improvement in learning outcomes in Cycle II with a percentage of 85.71%.